Perceived work ability at return to work in women treated for breast cancer: a questionnaire-based study - Musti, Muriel Assunta; Collina, Natalina; Stivanello, Elisa; Bonfiglioli, Roberta; Giordani, Stefano; Morelli, Carla; Pandolfi, Paolo (La Medicina del Lavoro, 2018)
Background: Breast cancer survivors often perceive reduced work ability upon returning to work. Objectives: To identify predictors of perceived reduced work ability following return to work among women treated for breast cancer and to describe workplace interventions and support after returning to work. Methods: A questionnaire was sent to 18-65 years-old women (no. 1578) treated for breast cancer and residing in the catchment area of the Bologna Local Health Authority between 2010 and 2012. The study population was identified through a Hospital Discharge Database. The questionnaires included items about personal characteristics, cancer and work-related factors, perceived work ability and the return to work process. A multivariable logistic regression analysis was performed to identify predictors of reduced work ability upon returning to work. Results: Among the 841 respondents, 503 questionnaires were evaluable. In the study, 43.5% of the respondents reported reduced work ability with respect to the pre-diagnosis period. Reduced work ability was more common in non-cohabiting (OR=1.81, 95%CI 1.10-2.98) than in cohabiting/married women, and after mastectomy (OR=2.77, 95%CI 1.26-6.11) than after breast-conserving surgery. Office staff/sales assistants and managers were less likely to report reduced work ability (OR=0.51, 95%CI 0.30-0.88 and OR=0.21, 95%CI 0.06-0.76, respectively) than labourers. Women who perceived reduced work ability reported more frequently adjustment of work assignments, consultation of an occupational physician, insufficient support from employers and colleagues and discrimination. Conclusions: Reduced work ability is commonly perceived among women who return to work after treatment for breast cancer. Occupational physicians and general practitioners should be aware of a wide range of factors influencing this perception in order to facilitate a successful return to work.